Untersuchungen zum Lautäußerungsverhalten von Wölfen (Canis lupus L.) und Haushunden (Canis lupus f. fam.) unter den Bedingungen der Gruppenhaltung - Meyer, Eva-Maria (2004)
This study examined the vocalisation behaviour in wolves and domestic dogs. The respective groups were kept in structured enclosures under comparable environmental conditions. The sounds obtained were classified on an auditory basis and named according to literature. Their respective physical parameters were analysed by means of sonography. For each sound, both the behaviour of the emitting animal and the reaction of the receiving animal were recorded. These behaviours were then classified according to the spatiotemporal parameters. The three groups investigated showed marked differences both in vocal repertoire as well as in social context in which certain vocalisations were emitted. In particular, barking was a trait peculiar to domestic dogs. Here, the German Shepherds were found to bark extraordinarily often and in a variety of social contexts. Furthermore, sounds occurring in different phonetic qualities were more common in domestic dogs than in wolves. For all groups, noisy sounds predominated in offensive aggressive communication, whereas harmonic sounds had an appeasing quality or emphasised the playful nature of an interaction. Inter-group differences in behaviour manipulation through aggressive communication were described. In the wolves and Malamutes, manipulation was much more finely graded than in the Shepherds. Long lasting and finely graded threatening rituals were particularly characteristic of wolves. Furthermore, differences were pointed out in quantity of vocalisation as well as in choice of vocalisation type in playful situations. Vocalisation was found to be highly dependent on social status in both the vocalising and the receiving animal. Only in the Shepherds, the physical structure of sounds was specific to the individual.